1997
DOI: 10.1002/(sici)1097-0231(199708)11:12<1342::aid-rcm972>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IgG glycation levels by matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry has been employed for the evaluation of the glycation level of IgG from healthy subjects and also from well- and badly-controlled diabetic patients. The measurements have been performed on untreated plasma protein fractions. The data obtained have shown that a clear mass increase, originating from non-enzymatic glycation processes, is observed in the case of diabetic patients: for well-controlled ones it is in the range 512-1565 Da, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…In vivo glycation of human IgG in healthy subjects and increased level in diabetic patients has been widely studied. [188][189][190][191][192][193] Glycation of monoclonal and polyclonal immunoglobulins of different species can also occur in vitro 188,189,[194][195][196][197][198][199][200][201][202][203] Andya et al 56 reported that storage of the spray-dried powder of a recombinant monoclonal antibody with a molar ratio of 300:1 lactose to antibody at 308C for 9 months caused a 100% glycation of this antibody as assayed by binding to a boronate affinity column. Harris 61 reported that glycation of lysine residues of the light chain and the Fab part of the heavy chain with a molecular weight increase of 162 Da is often observed by mass spectrometry analysis.…”
Section: Glycationmentioning
confidence: 99%
“…In vivo glycation of human IgG in healthy subjects and increased level in diabetic patients has been widely studied. [188][189][190][191][192][193] Glycation of monoclonal and polyclonal immunoglobulins of different species can also occur in vitro 188,189,[194][195][196][197][198][199][200][201][202][203] Andya et al 56 reported that storage of the spray-dried powder of a recombinant monoclonal antibody with a molar ratio of 300:1 lactose to antibody at 308C for 9 months caused a 100% glycation of this antibody as assayed by binding to a boronate affinity column. Harris 61 reported that glycation of lysine residues of the light chain and the Fab part of the heavy chain with a molecular weight increase of 162 Da is often observed by mass spectrometry analysis.…”
Section: Glycationmentioning
confidence: 99%
“…m/z 148800.Because valid results have been obtained in evaluating the number of glucose molecules that condense onto HSA, the same method was applied to evaluate the number of glucose molecules that condense onto IgG, so as to study its in vivo glycation (Lapolla et al, 1997a). Fourteen badly controlled non-insulin±dependent diabetic patients, 8 wellcontrolled non-insulin±dependent diabetic patients, and 8 controls were studied.…”
Section: Maldi In the Determination Of Glycation Levels Of Iggmentioning
confidence: 99%
“…The selection of an adequate sample preparation method relies primarily on the chemical characteristics of the targeted analytes. In some cases, biological samples can be directly analyzed without any pretreatment [198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213]. However, in most cases, simple sample preparation processes are involved, such as liquid-liquid extraction (LLE), solid-phase extraction (SPE), concentration, filtration, desalting, immunoaffinity capturing, and digestion.…”
Section: Methods For Improving Detection Efficiency Of Disease Biomarmentioning
confidence: 99%
“…Characteristic molecular profiles obtained by single-step MALDI-TOF/MS and MS/MS analyses were used for diagnosis of fucosidosis, aspartyl glucosaminuria, GM1 gangliosidosis, Sandhoff disease, α-mannosidosis, sialidosis, and type II and III mucolipidosis [202,203]. MALDI-TOF was also used to evaluate the degree of blood glycation of globins, which is involved in regulating diabetes [204][205][206][207][208][209][210][211][212]. Diluted whole blood samples were directly mixed with the organic matrix for MALDI-TOF/MS analysis [205].…”
Section: Direct Maldi-tof/ms Analysis Without Sample Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation